Employee Satisfaction at Maruti Suzuki India Limited - Ashima (Journal of Commerce and Trade, 2013)
This research paper focuses on Employee Satisfaction Level of Maruti Suzuki India Ltd. (MSIL). Job satisfaction can be defined as a person’s emotional response to aspects of work (such as salary, supervision, and benefits) or to the work itself. Job satisfaction as a combination of psychological, physiological and environmental circumstances that judge a person’s satisfaction with the job. Nine factors were identified that influenced job satisfaction. These were creativity, leadership, health and safety, teamwork, ethics and values, expectations and your role, recognition and rewards, training and policies and practices.Based on these parameters, a questionnaire was designed and administered to the employees of Maruti Suzuki India Ltd. (MSIL). Analysis was done to find employee satisfaction index (ESI) in Maruti Suzuki India Ltd. (MSIL). Also analysis was done on each of the nine parameter.Depending upon the Data analysis, general observations, suggestions and recommendations have been listed down in the closing note of the article.